Application of combination bubble liposomal amphotericin B and sonication has the dramatic effect on oral candidiasis. Issue 3 (May 2017) - Yamamoto, M.; Iwanaga, K.; Okinaga, T.; Ariyoshi, W.; Tominaga, K.; Nishihara, T.
Abstract: Objective: We previously reported that ultrasound-mediated destruction of microbubbles might be an innovative non-invasive drug delivery system. AmBisome is a single bilayer liposomal drug delivery system consisting of unilamellar bilayer liposomes with amphotericin B, an antifungal drug, intercalated within the membrane. In the present study, we developed a novel fungicidal drug delivery system using ultrasound and bubble liposomal amphotericin B prepared by enclosing perfluoropropane gas within AmBisome. Methods: Candida albicans growth inhibition was determined by measuring optical density (OD), counting the number of colony forming units (CFU), and measuring the colony diameters. Result: Treatment with bubble liposomal amphotericin B and ultrasound significantly reduced the OD, CFU and diameter of colonies of C. albicans compared with ultrasound alone, liposomal amphotericin B alone, bubble liposomal amphotericin B alone, liposomal amphotericin B with ultrasound. Conclusion: These results indicate that treatment with bubble liposomal amphotericin B with ultrasound efficiently inhibited the growth of C. albicans, suggesting this novel approach may have a beneficial effect on the treatment of oral candidal disease.